2008
DOI: 10.1163/156939308786389997
|View full text |Cite
|
Sign up to set email alerts
|

Standard Smith Chart Approach to Solve Exponential Tapered Nonuniform Transmission Line Problems

Abstract: In this paper, the analysis of standard Smith chart based on the theory of exponential tapered nonuniform transmission lines (ETNUTL in short) is presented. The approach using the standard Smith chart for ETNUTL is realized by a novel mathematical transformation. The standard Smith chart approach provides more flexibility to solve ETNUTL problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…On the other hand, observing from the right one, waves propagating in the forward and reverse directions possess Z − 0 and Z + 0 , respectively. Thus, interchanging of Z + 0 and Z − 0 in (8) and (9) with Z L = 0, Z in,R can be written compactly as shown in (12). Solving (10), (11) and (12) simultaneously, Z + 0 , Z − 0 and β can be determined analytically as follows [6]:…”
Section: Theory Of Ccitlsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, observing from the right one, waves propagating in the forward and reverse directions possess Z − 0 and Z + 0 , respectively. Thus, interchanging of Z + 0 and Z − 0 in (8) and (9) with Z L = 0, Z in,R can be written compactly as shown in (12). Solving (10), (11) and (12) simultaneously, Z + 0 , Z − 0 and β can be determined analytically as follows [6]:…”
Section: Theory Of Ccitlsmentioning
confidence: 99%
“…By definition, a CCITL possesses conjugate characteristic impedances Z ± 0 of waves propagating in the opposite directions along the transmission line. Examples of CCITLs are reciprocal lossless uniform TLs, nonreciprocal lossless uniform TLs [8][9][10], exponentially tapered lossless nonuniform TLs [2,11,12] and periodically loaded lossless TLs operated in passband [13][14][15][16][17][18]. Using the ABCD matrix technique, it can be shown that the equation of the input impedance at each terminal of loaded finite lossless periodic structures is in the same form as that of CCITLs [4].…”
Section: Introductionmentioning
confidence: 99%
“…Practical amplifier design, on the other hand, heavily relies on trade-offs and compromises as it inevitably involves integrating different subcomponents with different characteristics. The graphical tool such as the Smith chart has then been developed for a graphical-aided design of high-frequency devices such as microwave amplifiers in the Z 0 system [1][2][3], where Z 0 is the characteristic impedance (usually with a real value) of a transmission line (TL) of interest. The mathematical expressions for the graphical solutions have been further formulated and optimized in an effort to achieve certain properties of amplifiers [4].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a large community of researchers has paid a great attention to interconnects or TLs between these high-frequency sub-components as the TLs can greatly alter characteristics of the traveling signals and ultimately, the properties of amplifiers. TLs can typically be classified into several types such as reciprocal lossless and lossy TLs, nonreciprocal lossless [5][6][7][8] and lossy [2] TLs, and exponential tapered lossless nonuniform TLs [3,[9][10][11]. Some of these have already been employed for practical applications, while some novel ones have been modeled and fabricated; i.e., metamaterial TLs possessing negative refractive index and permeability [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of CCITLs are reciprocal lossless uniform transmission lines (TLs), nonreciprocal lossless uniform TLs, exponentially tapered lossless nonuniform TLs [3,8] and periodically loaded lossless TLs operated in passband [10][11][12][13][14][15]. In general, CCITLs are lossless and possess different characteristic impedances, which are complex conjugate of each other, for waves propagating in opposite directions.…”
Section: Introductionmentioning
confidence: 99%